Experiences of Registered Nurses in the Care of COVID-19 Patients: A Phenomenological Study - Salina, Sunil; Leena, K.C. (Journal of Health and Allied Sciences NU, 2021)
Introduction Coronavirus disease 2019 (COVID-19) is the infectious disease caused by the most recently discovered coronavirus. This new virus and disease were unknown before the outbreak began in Wuhan, China, in December 2019. COVID-19 is now a pandemic affecting many countries globally. The aim of this study was to examine the lived experiences of staff nurses who are involved in care of COVID-19 patients during COVID-19 outbreak in Kerala.Methods Qualitative phenomenological approach was used in this study. Data was gathered from six registered nurses through telephonic interview and video call. Moustakas's structured method of inductive data analysis was used in the study.Results Three themes were evolved from the current study. They are challenging profession, balancing profession with family, and from uncertainty to satisfaction.Discussion Findings drew from the current study highlight ever seen areas in health industry. The health workers are the major workforce in any epidemic outbreak. Concern to their health needs to be one of the higher priorities. It is ideal to talk about infection control and use of personal protective equipment. But the practical implication needs to be further explored in connection with infection control.
Keywords: COVID-19 and nursing; COVID-19 nursing challenges; Lived experiences caring COVID-19 positive; COVID-19 warriors